1996
DOI: 10.1016/0014-5793(96)01005-8
|View full text |Cite
|
Sign up to set email alerts
|

The p18 component of the multisynthetase complex shares a protein motif with the β and γ subunits of eukaryotic elongation factor 1

Abstract: tRNA synthetases is mediated by terminal polypeptide extenAbstract In higher eukaryotes, nine aminoacyl-tRNA synthetases form a multienzyme complex also comprising the three sions, which are dispensable parts of these enzymes for cataauxiliary proteins p18, p38 and p43, of apparent molecular lysis Materials and methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 27 publications
0
67
0
Order By: Relevance
“…Another potential ATM coactivator is p18 (AIMP3), which is a component of a translation complex and shows sequence homology to elongation factor subunit (EF-1) (Quevillon and Mirande, 1996), yet appears to function in the DNA damage response. Park et al (2005) showed that p18 regulates ATM-dependent p53 induction after DNA damage, and that ATM and ATR directly interact with p18 after UV and/or adriamycin treatment.…”
Section: Likely Candidates For Inactivators and Activators Of Atmmentioning
confidence: 99%
“…Another potential ATM coactivator is p18 (AIMP3), which is a component of a translation complex and shows sequence homology to elongation factor subunit (EF-1) (Quevillon and Mirande, 1996), yet appears to function in the DNA damage response. Park et al (2005) showed that p18 regulates ATM-dependent p53 induction after DNA damage, and that ATM and ATR directly interact with p18 after UV and/or adriamycin treatment.…”
Section: Likely Candidates For Inactivators and Activators Of Atmmentioning
confidence: 99%
“…The underlying basis of association has been demonstrated for several of the polypeptides to be the hydrophobic nature of extensions unique to the eukaryotic enzymes (reviewed in Mirande, 1991;Yang, 1996). In addition, specific sequence motifs have been identified in synthetase polypeptides and p l 8 that play a role in proteinprotein interaction (Quevillon & Mirande, 1996;Rho et al, 1996). The overall shape and size of the particle are known from electron microscopy studies (Norcum, 1989).…”
Section: K-rs:p38 D-rs:k-rs R-rs Dimer K-rs Dimer K-rs:q-rs E/p-mentioning
confidence: 99%
“…[1][2][3] The tRNA-binding domain associates with several aminoacyl-tRNA synthetases. On cleavage from the p43 component of the MSC, this domain becomes an independent domain with inflammatory cytokine activity.…”
Section: Introductionmentioning
confidence: 99%